Wing-size related habitat choice of Great Reed Warbler females: the role of habitat quality and management - Thomas O. MérÅ'; Antun Žuljević; Katalin Varga; Szabolcs Lengyel (Avian Conservation and Ecology, 2020)
Intersexual differences in habitat choice can arise if males and females differ in morphology, physiology, niche partitioning, or resource use, and can be influenced by variation in habitat structure, quality, and management. To better understand such intersexual differences, we studied habitat choice in female Great Reed Warblers (Acrocephalus arundinaceus), a long-distance migrant flagship species of lowland Palearctic reed (Phragmites australis) habitats. We compared wing length, a widely used proxy for individual quality in passerines, of females nesting in six types of differently managed reed habitats. Our dataset on 391 females nesting in 32 sites over 10 years showed that wing length was significantly greater in mining ponds and medium-sized canals than on large canals. Wing length was negatively related to water level fluctuation and females showed strong philopatry to the habitat type in which they were first captured. In comparison to our previous study on male habitat choice, this study found differences in habitat choice between the sexes. Although long-winged individuals in both sexes preferred habitats with stable water and avoided small canals, longer-winged males preferred large canals with little or no management, whereas long-winged females preferred medium-sized canals with some management. Although these results provide some support for intersexual niche segregation, it is also possible that long-winged females avoid large canals, in which nest parasitism by Cuckoos (Cuculus canorus) is frequent, and/or prefer managed, sparse reed beds with better maneuverability for foraging. Our studies suggest that males may primarily choose habitats with abundant old reed and singing perches, whereas females are less sensitive to environmental variation and may choose nest sites based on male quality or territory quality. For conservation, our studies imply that the maintenance of stable water levels, a low intensity of management and the elimination of Cuckoo perches are likely to benefit both long-winged males and females.